O tratamento com óleo de coco virgem (Cocos nucifera L.) melhora os parâmetros murinométricos, a função pulmonar e a reatividade traqueal de ratos Wistar obesos asmáticos - Pessoa, Rayane Fernandes (2022)
The incidence of obese asthmatic patients has increased in recent years, but little is known about the characteristics and therapeutic alternatives for the management of these associated comorbidities. A possible alternative for the treatment of obesity-exacerbated asthma is virgin coconut oil (VCO), which has already demonstrated a beneficial effect in a model of chronic allergic lung inflammation in guinea pigs. Therefore, the objective was to evaluate a possible effect of OCV on murinometric parameters, pulmonary function and tracheal reactivity in obese Wistar rats with asthma. Initially, a behavioral screening and evaluation of the toxicity of repeated doses of VCO in male and female rats (n = 5) was performed. To perform the other parameters, the animals were divided into four experimental groups (n = 6): control (CG), obese asthmatic (OAG) and obese asthmatic treated with VCO at doses of 1000 (OAVCOG1000) and 2000 mg/kg (OAVCOG2000). To induce this disorder, the animals received a high glycemic index and load (HGLID) diet for 16 weeks and were sensitized and nebulized with ovalbumin (OVA) during the last 21 days of the 16 weeks and the GOAOCV animals received the OCV in the last in the last 30 days. All experimental protocols were approved by CEUA/UFPB (9133040520). It was observed that VCO at doses of 1000 and 2000 mg/kg/day did not promote any behavioral change, did not induce deaths in animal, and there were no changes in feed consumption and weight of the animals. However, VCO (1000/2000 mg/kg/day) decreased fasting blood glucose in rats (95.2 ± 1.7 and 108.4 ± 2.1 mg/dL, respectively), when compared to CG (124 .3 ± 1.3 mg/dL). In female rats, only the dose of 2000 mg/kg/day (103.2 ± 3.4 mg/dL) reduced fasting blood glucose when compared to the CG (119.0 ± 1.1 mg/dL). Regarding the weight of the different organs, only the female rats treated with VCO 2000 mg/kg/day showed an increase in spleen weight (0.27 ± 0.01 g) and a decrease in liver weight (3.0 ± 0.1 g), when compared to the CG (0.2 ± 0.01 and 3.5 ± 0.14 g, respectively). In the evaluation of experimental obesity, it was observed that the ingestion of HGLID increased the body weight of the animals in the AOG (460.2 ± 21.0 g), when compared to the CG (365.2 ± 3.5 g), and the treatment with VCO at a dose of 2000 mg/kg/day (410.2 ± 9.8 g), prevented this increase. No changes were observed in daily feed intake between the experimental groups. Regarding murinometric parameters, treatment with VCO at doses of 1000 (95.3 ± 3.3 mg/dL) and 2000 mg/kg/day (104.2 ± 6.2 mg/dL) decreased fasting blood glucose. of these animals, compared to AOG (113.8 ± 6.1 mg/dL). Differently, in both doses, the VCO did not change the nasal length, Lee index, BMI and chest circumference. However, the dose of 2000 mg/kg/day (19.1 ± 0.2 cm) prevented the increase in abdominal circumference when compared to the CG (18.8 ± 0.3 cm). Regarding fat deposits, it was observed that treatment with VCO at doses of 1000 and 2000 mg/kg/day reversed the increase in this tissue caused by the ingestion of HGLID, in addition to reducing the adiposity index by about 43.5 e 64.1%. During the asthma induction period, the pulmonary function (tidal volume, respiratory rate and minute volume) of these animals was evaluated. It was observed that treatment with VCO at a dose of 2000 mg/kg/day reversed the reduction in respiratory rate and tidal volume caused by the disorder. Regarding the contractile reactivity of the trachea of asthmatic and obese rats, treatment with VCO (1000 and 2000 mg/kg/day) did not alter the contractions induced by KCl. When this contraction was induced by carbachol, only at the dose of 2000 mg/kg/day of VCO there was a reversal of the tracheal hyperresponsiveness caused by this disorder. It was further observed that treatment with VCO led to a reduction in the relaxing potency of nifedipine, but did not alter the relaxation induced by aminophylline. In view of this, it can be concluded that VCO can become a promising therapeutic alternative in the treatment of associated asthma and obesity.